Automatic chicken's fowl management system by using programmable logic controller (PLC) - Syed Abdul Rahman, Syed Abdul Mutalib Al Junid (2005)
The main purpose of this project is to fulfill the requirement to complete the degree courses in Electrical Engineering. Its objective is to develop problem solving, analysis, synthesis and evaluation skills in the field of Electrical Engineering in order to increase the performance of the Agriculture field. This project is designing of an automated chicken's fowl management system at lower cost by using PLC and simple devices in order to reduce the complexity of the daily jobs and increase the performance of the agricultural production. Users can operate the system by setting the ringing clock time then press ON the Start button for the system to start it's operation. In designing the system two path of work have been done. The first path is the hardware and second is the software. The hardware consists of 12VDC Motor, 6VDC Motor, Valve, Lamps and others. For the software, SYS WIN 3.4 is used. The program which controlled the system is written in ladder diagram. This program is entered to the PLC CPU using the window programming software called SysWin.